Interventions for Reducing Post-Traumatic Stress Disorder in Intensive Care Unit Survivors: A Scoping Review - Dadan Ramdani; Defa Larashati; Lurdes Acorta Freitas; Nur Azmi Lilikliswati; Suryani Suryani (Indonesian Journal of Global Health Research, 2024)
Post Traumatic Stress Disorder (PTSD) is a serious condition that patients often experience after undergoing intensive treatment in the ICU. Traumatic experiences during ICU care can cause significant and prolonged symptoms. PTSD has a major impact on patients' quality of life after discharge from the ICU. Various literatures have not comprehensively discussed PTSD in ICU survivors. Objective: To explore interventions in reducing PTSD symptoms in ICU survivors. Method: This study used the scoping review method with article searches from three databases, namely CINAHL, PubMed, and Medline. Keywords used included "ICU diaries," “interventions,” "post-ICU recovery program," and "PTSD." Inclusion criteria included original research articles with quasi-experimental or RCT designs, written in English, focusing on ICU survivors and the impact of PTSD, and a publication period of the last 10 years (2014-2024). Data extraction used manual tables. Data were analyzed using qualitative descriptive methods. Results: Eight relevant articles discussing interventions to reduce PTSD in ICU survivors were found. The study results indicate that there are two types of interventions, ICU diaries and post-ICU recovery programs, which are effective in reducing PTSD, anxiety, and depression symptoms in ICU survivors. The effectiveness of these interventions is supported by active family involvement, personalization of the intervention, and support from medical staff. Influencing variables include family involvement, method of intervention implementation, and continuous support from the medical team. Conclusion: This scoping review identifies that ICU diaries and post-ICU recovery programs are effective in reducing PTSD symptoms in ICU survivors. Further research is needed to explore the long-term effectiveness of these interventions and the development of best practices in post-ICU care.